Synthetic Lightweight Coarse Aggregate using Offshore Sand - Mohammad Amirulkhairi, Zubir; Muhammad Nazrin Akmal, Ahmad Zawawi; Mohd Fairuz, Azmi (Penerbit Akademia Baru, 2015)
Offshore sand is a capable alternative replacement for land aggregate in concrete. It is necessity for some country or regional where land aggregate is scarce and sometimes unavailable to be used for development but offshore sand is accessible for replacement. This paper reports about the production and usage of synthetic lightweight coarse aggregate produced using offshore sand (SYLCAG). It was produced with density of 1300 kg/m3 which is nearly 60% lighter than normal aggregate. This SYLCAG was used as a full replacement for coarse aggregate in concrete which then produced as a concrete with density almost 1900 kg/m3. The produced concrete did not have a good strength with design of 25 MPa concrete. However, it still has the potential to be develop with higher design and later used as structural concrete